2016
DOI: 10.3389/fnbeh.2016.00125
|View full text |Cite
|
Sign up to set email alerts
|

Echolocating Big Brown Bats, Eptesicus fuscus, Modulate Pulse Intervals to Overcome Range Ambiguity in Cluttered Surroundings

Abstract: Big brown bats (Eptesicus fuscus) emit trains of brief, wideband frequency-modulated (FM) echolocation sounds and use echoes of these sounds to orient, find insects, and guide flight through vegetation. They are observed to emit sounds that alternate between short and long inter-pulse intervals (IPIs), forming sonar sound groups. The occurrence of these strobe groups has been linked to flight in cluttered acoustic environments, but how exactly bats use sonar sound groups to orient and navigate is still a myste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 40 publications
5
71
0
Order By: Relevance
“…Bats dynamically adapt sonar call parameters to extract task-relevant echo information from the environment, and the temporal patterning of sonar calls (sonar sound groups, SSGs) is a component of the bat's adaptive vocal behavior. The production of SSGs has been recorded in echolocating bats in the field and in the laboratory Surlykke, 2001, 2010;Moss et al, 2006;Petrites et al, 2009;Surlykke et al, 2009;Aytekin et al, 2010;Hiryu et al, 2010;Falk et al, 2014;Kothari et al, 2014;Sändig et al, 2014;Wheeler et al, 2016). Insectivorous bats typically track moving prey, often with erratic trajectories, and in this study we show that bats increase the production of SSGs when target motion is unpredictable.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Bats dynamically adapt sonar call parameters to extract task-relevant echo information from the environment, and the temporal patterning of sonar calls (sonar sound groups, SSGs) is a component of the bat's adaptive vocal behavior. The production of SSGs has been recorded in echolocating bats in the field and in the laboratory Surlykke, 2001, 2010;Moss et al, 2006;Petrites et al, 2009;Surlykke et al, 2009;Aytekin et al, 2010;Hiryu et al, 2010;Falk et al, 2014;Kothari et al, 2014;Sändig et al, 2014;Wheeler et al, 2016). Insectivorous bats typically track moving prey, often with erratic trajectories, and in this study we show that bats increase the production of SSGs when target motion is unpredictable.…”
Section: Discussionsupporting
confidence: 54%
“…A related finding, reported by Sändig et al (2014), showed that bats performing a wire-avoidance task increased the production of SSGs with increasing task difficulty. In a more recent study, Wheeler et al (2016) reported that big brown bats not only increased the number of SSGs, but also the number of sonar vocalizations contained in each SSG, as they encountered greater clutter along their flight path. These observations support the hypothesis that the bat's production of SSGs serves to improve its spatiotemporal resolution of objects (targets or obstacles) in the environment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In flight, bats displayed natural adaptations in sonar behavior (Griffin, 1958;Simmons et al, 1979). Specifically, they increased echolocation pulse rate (PR) and decreased pulse duration (PD) as they approached objects or their landing points ( Figure 1E), and they also produced sonar sound groups (SSGs), or clusters of vocalizations, to inspect objects in space (Falk et al, 2014;Moss et al, 2006;Petrites et al, 2009;Sändig et al, 2014;Wheeler et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…This makes the acquisition rate highly accessible and allows us to answer questions on how bats adapt their sensory acquisition rate when orienting under different conditions. Many behavioral studies showed that bats often pattern their echolocation calls in form of groups (Amichai et al, 2015; Brinklov et al, 2011; Brinklov et al, 2009; Galambos and Griffin, 1942; Grinnell and Griffin, 1958; Kothari et al, 2018a; Luo et al, 2015; Roverud and Grinnell, 1985a; Roverud and Grinnell, 1985b; Wheeler et al, 2016; Wohlgemuth et al, 2016; Figure 1). Results from insectivorous bats led to the hypothesis that the emission of call groups may represent an adaptation to orient in complex environments (Falk et al, 2014; Fawcett et al, 2015; Kothari et al, 2014; Moss et al, 2006; Petrites et al, 2009; Sändig et al, 2014; Surlykke et al, 2009).…”
Section: Introductionmentioning
confidence: 99%